2006
DOI: 10.1007/s11274-006-9330-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mixed starter cultures fermentation on the characteristics of silver carp sausages

Abstract: To improve the quality and functionality and increase the utilization of silver carp (Hypophthalmichthys molitrix) muscle, three groups of silver carp sausages inoculated with the combinations of Staphylococcus xylosus-12 with Lactobacillus plantarum-15, Pediococcus pentosaceus-ATCC33316, and Lactobacillus casei subsp. casei-1.001, and a batch without any starter (control) were prepared. During the 48 h fermentation at 30°C, silver carp sausages inoculated with mixed starter cultures resulted in a rapid pH dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 43 publications
(45 reference statements)
5
40
1
2
Order By: Relevance
“…Initial average counts for both microorganisms found in surimi mixture sausages (1.94-2.69 log 10 CFU/g) were inferior to most of those obtained in other studies, where contamination levels around 3 log 10 CFU/g for total viable bacteria in frankfurter-type sausages (Metaxopoulos, Mataragas, & Drosinos, 2002), of 4-6.5 log 10 CFU/g for total viable counts in silver carp sausages (Hu, Xia, & Ge, 2007), 7.14 and 7.28 log 10 CFU/g for mesophiles, and 7.72 and 7.87 log 10 CFU/g for psychrotrophics, in retail chicken red and white sausages, respectively (Á lvarez-Astorga, Capita, Alonso-Calleja, Moreno, & Garcı´a-Ferna´ndez, 2002), were reported. Even contamination levels as high as 12.1 log 10 CFU/g were found (Vorster, Greebe, & Nortje´, 1994).…”
Section: Microbiological Analysiscontrasting
confidence: 71%
“…Initial average counts for both microorganisms found in surimi mixture sausages (1.94-2.69 log 10 CFU/g) were inferior to most of those obtained in other studies, where contamination levels around 3 log 10 CFU/g for total viable bacteria in frankfurter-type sausages (Metaxopoulos, Mataragas, & Drosinos, 2002), of 4-6.5 log 10 CFU/g for total viable counts in silver carp sausages (Hu, Xia, & Ge, 2007), 7.14 and 7.28 log 10 CFU/g for mesophiles, and 7.72 and 7.87 log 10 CFU/g for psychrotrophics, in retail chicken red and white sausages, respectively (Á lvarez-Astorga, Capita, Alonso-Calleja, Moreno, & Garcı´a-Ferna´ndez, 2002), were reported. Even contamination levels as high as 12.1 log 10 CFU/g were found (Vorster, Greebe, & Nortje´, 1994).…”
Section: Microbiological Analysiscontrasting
confidence: 71%
“…The firmness of the pickled vegetable decreased quadratically with fermentation time, as indicated by the increasing depth the probe could penetrate the tissue, that is from 43.16 to 59.31 in fermentation was higher than those in the batch that was inoculated with mixed cultures (Fig 1 B). The high population of LAB at the initial stage of fermentation had an important role in inhibiting growth of contaminants even after fermentation had started (Hu et al 2007;Rai et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that the faster the production of lactic acid, the faster the pH decreased (Tolonen et al 2002;Wiander and Ryhanen 2005), thus the faster the completion of In order to control the fermentation, LAB starter cultures have been used in the fermentations of sauerkraut, olives, cucumber, sausages, and other fermented products (Fleming et al 2001;Hu et al 2007;Rai et al 2006;Zdolec et al 2008). Volume 7, 2013 Microbiol Indones 5 were 3.2 and 3.3 (neither liked nor disliked).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Panelistler çiğ sucuklarda, kesit yüzey rengi ve görünüş, her iki grupta da pişmiş sucuklarda tat ve aroma, tekstür, genel beğeni açısından değerlendirme 13 . pH değerinin olgunlaşma süre since düşmesi ortamdaki laktobasil miktarının artışından kaynaklandığı düşünülmektedir.…”
Section: Duyusal Analizlerunclassified